A State of the Art of Communicative Competence Theory - Fauziati, Endang (Ahmad Dahlan Journal of English Studies, 2015)
What is actually involved in learning a foreign language? What kinds of knowledge and skill to be mastered? The answer to these questions deals with language competence, that is, the knowledge of the language and the ability to use that knowledge to interpret and produce meaningful texts appropriate to the situation in which they are used. It corresponds with Ellisâs (1996: 74) statement that the goal of learning a foreign language âis concerned with the ability to use language in communicative situationsâ and the point of language teaching is to help the students communicate or to develop what Hymes (1972) referred to as âcommunicative competenceâ.